2004
DOI: 10.1158/1078-0432.ccr-03-0807
|View full text |Cite
|
Sign up to set email alerts
|

Plasma and Cerebrospinal Fluid Population Pharmacokinetics of Temozolomide in Malignant Glioma Patients

Abstract: Purpose: Scarce information is available on the brain penetration of temozolomide (TMZ), although this novel methylating agent is mainly used for the treatment of malignant brain tumors. The purpose was to assess TMZ pharmacokinetics in plasma and cerebrospinal fluid (CSF) along with its inter-individual variability, to characterize covariates and to explore relationships between systemic or cerebral drug exposure and clinical outcomes.Experimental Design: TMZ levels were measured by high-performance liquid ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
324
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 424 publications
(339 citation statements)
references
References 50 publications
(45 reference statements)
6
324
1
Order By: Relevance
“…Similar results were seen in a primary GBM sample treated with or without 50 mM of TMZ (Supplementary Figure S3). Within specific subpopulations, the analyzed cells also presented a significant increase in other GSC markers, such as Sox2, Oct4, and Nestin (11,12, and 25% on average, respectively; ***Po0.001, Figure 1a and Supplementary Figure S2A). Additionally, they co-expressed markers of pluripotency and stemness -14% of GSCs co-expressed SOX2, 9% co-expressed Oct4, and 10% co-expressed Nestin (***Po0.001, Figure 1b and Supplementary Figure S2B).…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Similar results were seen in a primary GBM sample treated with or without 50 mM of TMZ (Supplementary Figure S3). Within specific subpopulations, the analyzed cells also presented a significant increase in other GSC markers, such as Sox2, Oct4, and Nestin (11,12, and 25% on average, respectively; ***Po0.001, Figure 1a and Supplementary Figure S2A). Additionally, they co-expressed markers of pluripotency and stemness -14% of GSCs co-expressed SOX2, 9% co-expressed Oct4, and 10% co-expressed Nestin (***Po0.001, Figure 1b and Supplementary Figure S2B).…”
Section: Resultsmentioning
confidence: 93%
“…The clinically relevant regimen for TMZ consists of 150-200 mg/m 2 /day, via oral administration, on days 1-5 of a 28-day cycle. 1 However, its peak concentration measured is only 50 mmol/l in patient's blood samples [9][10][11][12] and 5 mmol/l in the CSF. 12 Thus, it has been proposed that the intratumoral concentration may not exceed 50 mmol/l.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…shown that all CD133-positive glioblastoma cells tested are resistant to temozolomide-induced cell death at the maximum concentrations reached in the spinal fluid and in the plasma (21). In this study, CD133-positive glioblastoma cells were treated for 2, 4 and 6 days with increasing doses of TMZ.…”
Section: Evaluation Of Viability and Apoptotic Death Morphologically mentioning
confidence: 90%
“…1A). When these cells were subjected to cell death assay after treatment with clinically relevant concentrations ($50 lM) of temozolomide [18], we found that cell death was induced in close (inverse) In (E), the graph shows the percentage of dead cells (means þ standard deviations of three independent experiments). *, p < .01, **, p < .05, n.s., not significant.…”
Section: Mgmt Expression Level Is a Critical Determinant Of Temozolommentioning
confidence: 99%